On Maximal and Minimal Solutions for Set-Valued Differential Equations with Feedback Control - Ngo Van Hoa; Nguyen Dinh Phu (Abstract and Applied Analysis)
In this paper, we present the existence of extremal solutions of set-valued differential equations with feedback control on semilinear Hausdorff space under Hukuhara derivative which is developed under the form DHX(t)=F(t, X(t),H(t,X(t))), X(0)=X0,  for all t∈[0,T] with the monotone iterative technique and we will verify that monotone sequence of approximate solutions converging uniformly to the solution of the problem, that is useful for optimization problems.